Histomorphological Spetrum of Breast Lesions - Parajuli, S; Koirala, U; Khatri, R; Acharya, L; Suwal, A (Journal of Nepal Health Research Council, 2011)
Background: Cancer of the breast is the second most common cause of cancer in women. Mass in the breast, whether benign or malignant is a cause of anxiety to the patients and the family members. All breast lumps are considered to be carcinomas until proved otherwise and are the causes of concern both for the patient and surgeon. Methods: This is a retrospective study conducted in Kathmandu Model Hospital for a total duration of three years from August 2007 to August 2010. Results: 114 sample of breast tissue sent for histopathology were studied. Peak incidence of benign lesion was in between 21-30 years and malignant lesions in between 31-50 years. No breast lesions were seen in the first decade of life. Cancer of the breast was seen in 12.28% of cases. Fibroadenoma and fibrocystic disease were the commonest benign lesion and infiltrating ductal carcinoma was the commonest malignant lesion. Specimens from 10 male breasts were received. Gynaecomastia was the most common lesion encountered in males. Infiltrating ductal carcinoma was seen in a 70 year old male. Conclusions: Breast cancer is one of the commonest causes of breast lump particularly in women and is growing public health problem in Nepal. Keywords: breast cancer, breast lumps, excisional biopsy.